Magnetocaloric effect in bamboo-grained Ni-Mn-Ga microwires over a wide working temperature interval. (May 2020) - Qian, M.F.; Zhang, X.X.; Li, X.; Zhang, R.C.; Martin, P.G.; Sun, J.F.; Geng, L.; Scott, T.B.; Peng, H.X.
Abstract: Bamboo-grained Ni-Mn-Ga microwire is promising for achieving considerable magnetic-field-induced strain due to less neighboring grain constraints to the twin boundary motion. Such reduction of resistance to interface motion also favors the reduction of hysteresis in magnetic refrigeration. Here, bamboo-grained Ni-Mn-Ga microwires were successfully synthesized by a melt-extraction technique and subsequent high temperature heat treatment at 1323 K for 3 h under Argon atmosphere. Corresponding microstructure, martensite transformation (MT) behaviors and magnetocaloric properties were investigated. The high specific surface area of the microwires favored the element evaporation at high temperature, leading to a heterogeneous composition state, which is responsible for the MT temperature (range) change and the multi-variants state in the bamboo-grained microwires. Nearly no magnetic hysteresis loss was obtained. The increased compositional variation led to the partial overlap of the MT and the magnetic transition, resulting in the improvement of the working temperature interval 71 K and net refrigeration capacity 255 J/kg under μ 0 H = 5 T, which is heretofore the largest value reported in Ni-Mn-based Heusler alloys. When utilized as refrigerant in a cooling device, such small-sized microwires can increase the contacting area between the material and the heat-transfer agent, which helps the heat exchange and thus improve the refrigeration efficiency. Graphical abstract: Unlabelled Image Highlights: Bamboo-grained Ni-Mn-Ga microwires were prepared and negligible magnetic hysteresis was attained. No texture was obtained in the bamboo-grained microwire at austenite state. Multi-variants state was obtained in each grain due to the compositional variation. Working temperature interval 71 K and net refrigeration capacity 255 J/kg under 5 T were achieved.